Biomechancal response of new femoral components for patellofemoral arthroplasty - Castro, André (2011)
One of the major reasons for the failure of currently available knee implants is the stress shielding effect. The implant acts as a “shield of loads”, which means that loads are not distributed throughout the bone tissue and, consequently, the rate of bone remodeling decreases. The purpose for this work was to analyze the influence of the geometry and rigidity of the bone-implant interface on the stress shielding effect and on the stability of the prosthesis, applying the Finite Element Method. The results showed that elastic strain is lower on bone areas close to the studied models of patellofemoral prosthesis, on the period after the implantation. When the lifetime of the implant advances, bone rupture by fatigue may occur, due to elevated strain, particularly on the models with fixation pins for the prosthesis. Additionally, contact analyses showed that stability is best promoted without fixation pins.